Light-emitting diodes as visual attractants to phlebotomine sand flies (Diptera: Psychodidae): A mini-review - da Rocha Silva, Flávia Benini [UNESP]; Machado, Vicente Estevam [UNESP]; Pinto, Mara Cristina [UNESP] (Elsevier, 2023)
Phlebotomine sand flies are responsible for the transmission of different pathogens, including flagellate protozoan of the genus Leishmania. To locate a vertebrate host, females use chemical cues called kairomones, which are also used by males and females to locate carbohydrate sources of food. In addition to these chemical cues, visual cues (such as light and color) can play a key role in determining host location. In this way, incandescent white light is widely used to capture these insects in the field, being more recently replaced by light-emitting diode (LEDs) technology, which can be used with different colors. In this review, we summarize the main results of the use of LEDs as attractants for sand flies. Considering the different LEDs colors, blue and green are responsible for catching the highest number of sand fly species, especially for field trials conducted in New World countries. The intensity of light colors is an important factor to be considered, but so far little explored. In general, the use of LEDs can be considered as a feasible tool for the improvement of light traps. Future research is required to assert the contribution of different colors individually, in different combinations and intensities, as well as the possible synergistic effect of LEDs in association with attractive compounds in the behavior of sand flies.
Keywords: Colors; LEDs; Light trap; Phototaxis